Bioethics and Paideia - Željko Kaluđerović; Zorica Kaluđerović Mijartović (Pannoniana, 2020)
The process of spreading scientific and technical achievements is an anthropological phenomenon that is difficult to stop, because this is, as it were, the ontological determinant of modern man. Societies, especially over the past two centuries, have been facing the challenging task of balancing between the scientific freedom of research and preservation of social norms and values. The authors are of the opinion that the existing predominantly heteronomous constraints, although necessary, are not sufficient if the scientists themselves do not develop the awareness that they should follow the general humanistic moral principles and principles of scientific criticality. Finally, in the ambivalent period of strengthening the social and technical-technological effects of science, it is necessary to bioethically codify the issue of social responsibility of scientists which, due to its adequate internalisation, should be an integral part of their upbringing and education from the earliest days.